Meningkatkan UMKM Di Pulau Alor Dalam Novel Swarna Alor: Impian Di Langit Timur Karya Dyah Prameswarie (International Forum of Researchers and Lecturers, 2024)
Abstract.This research aims to describe UMKM marketing strategies in a literary work. The literary work used in this research is a novel entitled Swarna Alor by Dyah Prameswarie. The method used is a qualitative method with a descriptive approach. The results of this research show that the people of Alor Island have great potential to develop the village economy through UMKM. Supporting factors in community development in the economic sector include abundant natural resources and fairly high community participation. Meanwhile, the inhibiting factor is limited marketing facilities